Reading Luke-Acts in the pentecostal tradition - Mittelstadt, Martin William (Cleveland, Tennessee : CPT Press, 2010)
"...Martin Mittelstadt has undertaken an extensive examination of Pentecostal scholarship with an eye toward assessing the influence of Luke-Acts upon it. Beginning with Azusa Street and continuing to the present, Mittelstadt: 1(traces the emergence of Pentecostal scholarship in the academic market-place with the various reponses to the catalytic work of James D.G. Dunn, 2(examines the influence of Luke-Acts on narrative theology, missiology, healing and exorcism, the role of women, spiritual formation, and Oneness theology, and 3(identifies Pentecostal contributions in the area of social ethics, peace-making, suffering and persecution, ecumenism, globalization, and post-modernity. The work concludes with observations on possiblities for future engagement and an extensive bibliography. Mittelstadt proves to be an authoritative guide for all interested in how Pentecostals have read and continue to read Luke-Acts. -- Cover.
Introduction: twentieth century trajectories--History and trajectory of Pentecostal contributions to Luke-Acts research--The current status of Luke-Acts research: observations and possiblities--A not so final word.
Includes indexes.
Bibliography: p. 170-210.
Keywords: Holy Spirit -- Biblical teaching; Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Bible. -- Theology; Bible. -- Theology; Baptism in the Holy Spirit -- Biblical teaching; Holy Spirit -- History of doctrines; Pentecostalism--History of doctrines